Efektivitas Bauran Pemasaran Terhadap Tingkat Kunjungan Ekowisata di Kawasan Oi Marai Resort Kawinda To’i Taman Nasional Tambora - Khusnul Hayati; Hairil Anwar; Endah Wahyuningsih (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This study aims to analyze the Effectiveness of Marketing Mix on the Level ofEcotourism Visits in the Oi Marai Area, a tourist attraction in Kawinda To'i Village,Tambora District, Bima Regency. Marketing, which includes a marketing mix strategy, isused as the main tool to attract tourists, focusing on products, prices, places, andpromotions. Using a descriptive research method, researchers selected 48 respondentsconsisting of tourists and area managers using the Purposive Sampling technique. Based onthe results of the study, it was found that the level of effectiveness of Oi Marai tourismmarketing was very high, with an effectiveness ratio reaching 90% and above in 2019-2020and increasing to 100% and above in 2021-2022. Partially and simultaneously, all elementsof the marketing mix were proven to have a significant influence on the level of tourist visits,with a significant value of less than 0.05. These results indicate that the marketing strategyimplemented in Oi Marai was successful in attracting tourist visits and increasing theeffectiveness of local tourism.